A comparable rate of levator ani muscle injury in operative vaginal delivery (forceps and vacuum) according to the characteristics of the instrumentation. (22nd February 2019) - García‐Mejido, José A.; Fernández‐Palacín, Ana; Bonomi Barby, María J.; Castro, Laura; Aquise, Adriana; Sainz, José A.
Abstract: Introduction: Forceps delivery is associated with a high rate of levator ani muscle (LAM) trauma (avulsion) at 35%‐65% whereas data on avulsion rates after vacuum delivery vary greatly. Nevertheless, a common characteristic of all previous studies carried out to evaluate the association between instrumental deliveries (forceps and vacuum) and LAM avulsion, is the fact that characteristics of the instrumentation have not been described or evaluated. The objective of this study is to compare the rate of LAM avulsion between forceps and vacuum deliveries according to the characteristics of the instrumentation. Material and methods: Prospective, observational study, including 263 nulliparous women, who underwent an instrumental delivery with either Malmström vacuum or Kielland forceps. The characteristics of the instrumentation, position (anterior position and other position) and height of the fetal head at the moment of instrumentation (low instrumentation [vertex at +2 station] and mid‐instrumentation [head is involved but leading part above +2 station]) were assessed. Evaluation of LAM avulsion was performed at 6 months postpartum by three‐/four‐dimensional transperineal ultrasound. Using the multi‐view mode, a complete avulsion was diagnosed when the abnormal muscle insertion was identified in all three central slices, that is, in the plane of minimal hiatal dimensions and the 2.5‐mm and 5.0‐mm slices cranial to this one. To detect a 30% or 15% difference in the LAM injury rate, with 80% power and 5% α‐error, we needed, respectively 42 and 99 women per study group. Results: In all, 263 nulliparous individuals have been evaluated (162 vacuum deliveries, 101 forceps deliveries). Instrumentation in an occipito‐anterior position was more frequent in vacuum deliveries (75.3% vs 56.4%, P  = .002), whereas other positions were more frequent in the forceps deliveries group (24.7% vs 43.6%). No statistically significant differences were noted regarding the height of the fetal head at the moment of instrumentation. No statistically significant differences were found in the presence of LAM avulsion (41.4% vs 38.6%) between vacuum and forceps deliveries. The univariate analysis of the crude odds ratio was 1.17, 95% CI 0.67‐1.98, P  = .70 for the avulsion of the LAM and the multivariate of the adjusted OR 0.90, 95% CI; 0.53‐1.55, P  = .71. Conclusions: We consider that, in our population, LAM avulsion rate should not be a factor taken into account when choosing the type of instrumentation (Malmström vacuum or Kielland forceps) in an operative delivery.